Model for estimating of population abundance using line transect sampling - Noryanti, Muhammad; Saeed, Gamil Abdulraqeb Abdullah; Chuan, Zun Liang; Wan Nur Syahidah, Wan Yusoff; Mohd Zuki, Salleh (IOP Publishing, 2017)
Today, many studies use the nonparametric methods for estimating objects abundance, for the simplicity, the parametric methods are widely used by biometricians. This paper is designed to present the proposed model for estimating of population abundance using line transect technique. The proposed model is appealing because it is strictly monotonically decreasing with perpendicular distance and it satisfies the shoulder conditions. The statistical properties and inference of the proposed model are discussed. In the presented detection function, theoretically, the proposed model is satisfied the line transect assumption, that leads us to study the performance of this model. We use this model as a reference for the future research of density estimation. In this paper we also study the assumption of the detection function and introduce the corresponding model in order to apply the simulation in future work.